ANALYSIS OF PALATAL RUGAE PATTERN IN POPULATION OF ABBOTTABAD: A FORENSIC STUDY - Jadoon, Omair Khan; Zaman, Masud uz; Zaman, Fasseh uz; Khan, Delawar; Farooq, Umer; Seema, Nighat; Ahmed, Iftikhar (Journal of Ayub Medical College Abbottabad, 2018)
Background: Identification of unknown dead bodies' especially bony remains is done by different methods like DNA typing, Finger printing, Dental and other skeletal data, facial reconstruction and rugae pattern study. Palatal rugae pattern study or Ruguscopy gives a unique method of identification in cases of skeletal remains due to its uniqueness, resistance to heat, and stability throughout life. Methods: This simple random sampling was carried out on 102 study models (casts of palate) of patients having 880 rugae patterns above 20 years of age in Khan Dental Clinic near Ayub Medical College, Abbottabad. The study is based on classification given by Thomas et al. Casts were taken from palate and then individual casts studied for rugae pattern. They were classified and variations studied for uniqueness results: Each individual had different set of palatal rugae which are not same, in all its dimensions like size shape number etc. Conclusion: With the help of this study we can conclude that Palatal rugae pattern give unique method for individual identification. Keywords: Plica palatine; Palate; skeletal remains; palatoscopy; Dental